ANALISIS PERSEPSI DAN STRATEGI PENGEMBANGAN EKOWISATA PANTAI LEMO-LEMO KELURAHAN TANAH LEMO KECEMATAN BONTO BAHARI KABUPATEN BULUKUMBA - Nurazizah Nurazizah; Muhammad Kasnir; Asbar Asbar (Fakultas Perikanan dan Ilmu Kelautan Universitas Muslim Indonesia Makassar, Sulawesi Selatan, 2024)
The purpose of this study is to determine the Potential, Perception and Ecotourism Development Strategy of Lemo-Lemo Beach, Tahah Lemo Village, Bonto Bahari District, Bulukumba Regency. This research was conducted using qualitative descriptive method. This study was conducted from October to November 2023. The results showed that the potential for the development of lemo-lemo beach is very suitable (S1) to be developed into beach tourism based on the tourism suitability index (IKW), which is 91%. Public perception of the development of Lemo-Lemo beach tourism are: Attractiveness 83.64%, Accessibility 44.51%, Condition of tourism objects 59.73%, Supporting facilities 62.63%, complementary facilities 39.12%, So the overall perception of the Lemo-Lemo beach community category agrees with a percentage of 100% and this indicates that Lemo-Lemo beach tourism deserves to be developed. The Lemo-Lemo beach tourism attraction development strategy must promote the potential of beach tourism, improve the development of facilities and infrastructure as well as accessibility and cooperate with local governments and related agencies.